Advanced In Situ Soil Water Sampling System for Monitoring Solute Fluxes in the Vadose Zone. Issue 1 (25th July 2019) - Reck, Arne; Paton, Eva; Kluge, Björn
Abstract : Core Ideas: The monitoring system synchronizes soil water extraction with real drainage periods. It is remote controllable and has SMS notification in case of automated sampling initiation. It is easy to duplicate using commonly available measuring equipment. The system can monitor field soil solute fluxes, such as contaminant migration. To estimate potential risks of groundwater contamination, national and international environmental legislation stipulates standard values referred to pollutant contents in the soil and more rarely referred to loads in the soil leachate. Although in situ soil leachate analysis yields more realistic drainage water quality estimates than soil contamination level–derived estimates, there is no existing standard for how to explicitly sample soil leachate for the required contaminant migration detection. The objective of this study was to overcome current limitations of soil seepage sampling for detecting a contaminant migration in the unsaturated zone by introducing a technical solution that automatically restricts soil water extraction to drainage periods using active devices such as suction cups. Sampling is triggered by a moisture threshold parameterized according to the respective soil water retention properties defining the onset of a drainage period. We tested our sampling approach on two different bioretention systems in Germany for stormwater drainage quality analysis out of the upper soil layer. We present the monitoring results of the 4‐mo testing phase containing 19 individual storm events illustrating the fundamental functioning of the in situ soil leachate sampling system under different climatic conditions. The results clearly demonstrate the feasibility of restricting soil water extraction to drainage periods by means of actual soil moisture measures and indicate a general transferability of our approach. Our approach is easily duplicable, based on the included technical description, for further studies requiring explicit soil leachate sampling and is likely to help improve the reliability of field‐monitored pollutant migration from contaminated sites.